Asian development outlook (ADO) 2017 transcending the middle-income challenge. (Asian Development Outlook, 2017)
Decades of rapid growth transformed developing Asia from a low income region to middle income. Sustaining growth to power the transition to high income will depend on much greater improvement in productivity. Innovation, human capital, and infrastructure are the three pillars of productivity growth. Supportive institutions and policies, underpinned by macroeconomic stability, can strengthen all three pillars. Asia dynamic track record suggests that attaining high income status, while challenging, is achievable.